2015
DOI: 10.1371/journal.pone.0136706
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Level and Dyslipidemia in Rural Elderly Chinese

Abstract: ObjectiveHigher selenium level has been hypothesized to have the potential to reduce the risk of cardiovascular diseases including dyslipidemia. However, results from previous studies are inconsistent. This study aims to determine the association between selenium level and dyslipidemia in elderly Chinese with relatively low selenium status.MethodsA cross-sectional study of 1859 participants aged 65 or older from four rural counties in China was conducted. Serum total cholesterol (TC), triglycerides (TG), high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 58 publications
1
12
2
2
Order By: Relevance
“…The selenium intake among cohort participants in Golestan was greater than the US RDA (55 μ g/day) in our previous study . Nail selenium concentrations among controls in our study were high in comparison with previous studies which targeted other diseases in other population (Table ) . Our findings suggest that selenium deficiency is not a risk factor for the high incidence of ESCC in northeastern part of Iran.…”
Section: Discussioncontrasting
confidence: 76%
“…The selenium intake among cohort participants in Golestan was greater than the US RDA (55 μ g/day) in our previous study . Nail selenium concentrations among controls in our study were high in comparison with previous studies which targeted other diseases in other population (Table ) . Our findings suggest that selenium deficiency is not a risk factor for the high incidence of ESCC in northeastern part of Iran.…”
Section: Discussioncontrasting
confidence: 76%
“…A study carried out in Changsha, China, among 3500 persons aged 65 and over also reported high serum cholesterol, triglyceride, and LDL as 25.31%, 26.54%, and 16.65%, respectively [8]. Another study carried out among rural elderly in China reported the similar prevalence of high cholesterol (18.13%), while prevalence of high triglyceride (12.21%), low HDL cholesterol (32.76%), and high LDL cholesterol (13.23%) was lower compared to our findings [9]. Asian Indians have an abnormal fat distribution which makes it more prone to dyslipidemia [10].…”
Section: Discussionsupporting
confidence: 50%
“…A high Se-status could have adverse cardio-metabolic effects of on cardiovascular diseases (CVD) [ 89 ]. Higher plasma Se levels were associated with increased total lipoproteins and low density lipoprotein (LDL), and the risk of dyslipidemia [ 90 , 91 ]. A potential explanation between high Se and high lipid levels is a shared enzyme, 3-hydroxy-3-methyglutaryl coenzyme A reductase that can act through the mevalonate pathway that affects both Se and lipids [ 91 ].…”
Section: Reductive Stress In Inflammation Related Diseasesmentioning
confidence: 99%